A Comparison of Zika Virus and COVID‐19: Clinical Overview and Public Health Messaging. (7th June 2021) - McBroom, Kelly
Abstract: Prenatal exposure to the Zika virus (ZIKV) is associated with a significant risk of neurological impairment for infants. ZIKV serves as a cautionary model with significant parallels to the current coronavirus 2019 (COVID‐19) pandemic. A limited literature search was performed to compare and contrast the clinical and psychosocial aspects of infection with ZIKV and COVID‐19. There are significant parallels between ZIKV disease and COVID‐19 in terms of limited diagnostic techniques, therapeutics, and prognostic uncertainties. Both infections are associated with a significant risk of adverse outcomes for either the pregnant individual or the fetus. Existing social and economic inequalities amplify the risk burden of ZIKV disease and COVID‐19 in vulnerable communities. Although each pathogen has unique features, there are underlying common principles with regard to the recognition, communication, and mitigation of risk of infection. Misinformation spread by social media platforms has undermined public health efforts and patient adoption of recommended mitigation strategies. Health care providers can provide partnership, social support, and evidence‐based information to enhance health‐seeking behaviors, thereby minimizing the risks for pregnant and reproductive‐aged persons.